2018
DOI: 10.1161/hypertensionaha.118.11860
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Causes Biphasic STAT3 Activation Through TLR4 to Initiate Cardiac Remodeling

Abstract: Evidence indicates that Ang II (angiotensin II) activates STAT3 (signal transducer and activator of transcription 3) in cardiomyocytes. However, the mechanisms underlying STAT3 activation and downstream responses are not fully known. In this study, we show that Ang II caused biphasic STAT3 activation in cardiomyocytes. A rapid and early activation was mediated by direct association between TLR4 (toll-like receptor-4) and STAT3. This early activation increased IL-6 (interleukin-6) production, which in turn, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…TLRs are a pattern recognition receptor (PRR) that triggers host inflammation. TLRs also play a crucial role in pathological cardiac hypertrophy 35 . TLR4 mediates Ang II-induced pathological cardiac hypertrophy and HF 36 .…”
Section: Discussionmentioning
confidence: 99%
“…TLRs are a pattern recognition receptor (PRR) that triggers host inflammation. TLRs also play a crucial role in pathological cardiac hypertrophy 35 . TLR4 mediates Ang II-induced pathological cardiac hypertrophy and HF 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies also showed that inhibition of JAK2 and AT 1 Rs significantly reduced the development of both hypertension and proteinuria in diabetic nephropathy [13,27]. Ang II caused biphasic STAT3 activation in cardiomyocytes, an effect that was mediated by IL-6 [28]. These findings suggest a crucial role of JAK2/STAT3 in the development of Ang II-mediated hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The general procedure for Western blot analysis was described in our previous publication. 17 Antibodies against P-FGFR1, FGFR1, transforming growth factor-β (TGF-β), collagen (col) IV, Bax, Bcl-2, IκB-α, P-TGF-β activated kinase 1 (TAK1), TAK1, GAPDH and the secondary horseradish peroxidase-conjugated antibody were obtained from Santa Cruz Biotechnology (Santa Cruz, CA). Antibody against Ub was obtained from Cell Signaling Technology (CST, CA, USA).…”
Section: Western Blotting and Co-immunoprecipitationmentioning
confidence: 99%
“…The general procedure for RT-qPCR was described in our previous publication. 17 Primers for genes including TGFβ, Col-IV, Bax, Bcl-2, TNF-α, IL-6 and β-actin were synthesized by Invitrogen (Invitrogen, Shanghai, China). The primer sequences used are shown in Table S1.…”
Section: Real-time Quantitative Qpcrmentioning
confidence: 99%